The self-similar stratified inner-shelf response to transient rip-current-induced mixing. (19th March 2021) - Grimes, Derek J.; Feddersen, Falk
Abstract: Abstract : The stratified inner-shelf response to surf-zone-generated transient rip currents (TRC) is examined using idealized simulations with uniform initial thermal stratification dT_0/dz, with initial temperature T 0 and vertical coordinate z, or initial squared buoyancy frequency N_0^2, varying from unstratified to highly stratified ( 0.75^° C m^-1 ). The TRC-induced depth-integrated cross-shore eddy kinetic energy flux is independent of dT_0/dz and decays to near zero within 4L_SZ (surf-zone width L_SZ=100 m). Cross-shore inhomogeneous TRC mixing causes shoreward broadening isotherms, driving a near-field inner-shelf overturning circulation and a far-field geostrophic along-shore velocity that strengthen with dT_0/dz . TRC mixing mostly (90 %) increases background potential energy (BPE) and also available (APE, 10 %) potential energy, driving inner-shelf mean circulation. The specific BPE zero-crossing depth d_s collapses the near-field 3 -layer cross-shore velocity, using an intrusive gravity current scaling (d_s N_0) . The approximately steady exchange flow exports low-stratification fluid ( N/N_0≈ 1/2 ) at a depth z/d_s≈ -1, re-supplying the TRC region with stratified fluid from above/below, similar to localized mixing laboratory experiments. Offshore of ≈ 5L_SZ, a self-similar far-field intrusion with characteristic isotherm slope d_s/L_R (Rossby deformation radius L_Rd_s f/N_0 ) is in approximate geostrophic balance with the non-dimensional along-shore velocity. Inner-shelf near-field and far-field horizontal length scales vary as x/d_s and x/L_R, respectively. The length scale d_s is related to the work performed by TRC mixing using an idealized well-mixed wedge geometry. Idealized analytical scalings are qualitatively consistent with modelled BPE and APE distributions. Thus, the self-similar stratified inner-shelf response to TRC-driven mixing depends on key dimensional parameters N_0 and d_s .